The Influence of Entrepreneurial Education, Social Support and Passion for Government Support as Moderating Variables on Entrepreneurial Behavior: Study of MSME Players in Sorong City - Rahma Karnia Lakamudi; Budi Santoso; Agung Wahyu Handaru (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to determine the influence of entrepreneurship education, social support and passion with government support as moderating variables on entrepreneurial behavior in the study of MSMEs in Sorong City. This research uses a quantitative type of research using a population of 6,886 people with a sample of 380 MSMEs in the city of Sorong. The data collection technique uses a questionnaire. Data analysis uses Structural Equation Modeling (SEM) with the AMOS 21 program. The results show that entrepreneurship education does not have a positive and significant effect on entrepreneurial behavior, social support has a positive and significant effect on entrepreneurial behavior, passion has a positive and significant effect on entrepreneurial behavior, government support moderates the influence of entrepreneurial education on entrepreneurial behavior, government support moderates the influence of social support on entrepreneurial behavior and government support moderates the influence of passion on entrepreneurial behavior.